Contestation on the meanings of and their effect on interpretation of the notion of Local Economic Development - Mqedlana, Lwandlekazi Vuyokazi (My University, 2015)
Despite sustained efforts to implement Local Economic Development (LED) in South Africa, this has not met with the success that was hoped for. In part, this stems from the diverse conceptualizations and interpretations of LED. The research report sought to interrogate these diverse interpretations and meanings with the objective of establishing the impact that such ‘differences’ might have on the policy and actual implementation of LED in rural and urban municipalities in South Africa. To achieve this objective, the project utilized a qualitative survey, focusing on the cases of the urban-based UMhlathuze Local Municipality and the ruralbased Richmond Local Municipality. The study found that the diverse global and national ‘differences’ surrounding LED discourse have impacted significantly on how LED policies and strategies are implemented in South Africa. This includes a significant level of confusion regarding the most suitable implementation strategy. The study concludes that consensus on the definition of LED and the theoretical framework that informs LED should be reached within the South African policy context.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2014.